Understanding the Jal el-Bahr Storage-Jar Assemblage - Ariel, Donald T. (Journal of Hellenistic Pottery and Material Culture, 2019)
In my research of the archive of 2.048 sealings uncovered at Tel Kedesh in Upper Galilee, Israel, I encountered articles written by the Lebanese archaeologist Ibrahim Kawkabani, and published in ›Archaeology and History in Lebanon‹. In those detailed articles is a wealth of information about finds from »systématiquement« excavations (elsewhere described as »some soundings«) – directed by Maurice Chéhab? at Jal el-Bahr, a site at the northeastern entrance to ancient Tyre, beginning in 1972. The publication of such a great amount of new inscribed Phoenician material is not only relevant to my research on the inscribed material from Kedesh, but also important to understanding the workings of Tyre, its bureaucracy and administration, especially in the second century BCE.